ANALISIS RUGI-RUGI HEAT RATE PLTU BANTEN 3 LONTAR AKIBAT DEVIASI PARAMETER PADA KONDISI AKTUAL MENGGUNAKAN ANALISIS GAP: Heat Rate Losses Analysis of Banten 3 Lontar PLTU due to Deviation Parameter on Actual Condition using Gap Analysis - Wahyudi, Teguh; Yuriadi Kusuma (Jurnal Konversi Energi dan Manufaktur, 2024)
Steam power plant (PLTU) is one type of energy conversion technology to generate electricity from fossil materials. The performance of a PLTU unit will begin to decline as the unit ages. In addition to age, performance degradation can also be caused by deviation of operating parameters, which can cause heat rate losses. The purpose of this study is to determine the performance of PLTU Banten 3 Lontar unit 2 by analyzing heat rate losses due to parameter deviations according to actual conditions and calculating cost savings and possible improvements. The research methodology used is an evaluation method where the actual data of operating parameters will be compared with the baseline data. The comparison will produce a deviation value, which is then used to obtain the value of heat loss, cost loss, and improvement recommendations for the plant. Baseline data is obtained from the interpolation equation of commissioning testing at 3 different variation loads. From the study, it is known that there was an increase in Nett Plant Heat Rate (NPHR) with an average of 561 kCal / kWh. The increase in NPHR occurred due to heat rate losses, where the decrease in turbine HP efficiency was the main cause, with an average loss of 87.96 kCal / kWh or 24.53% of total losses. Assuming that all heat rate losses during testing can be corrected, the average potential energy savings per day is 8,604,802 kCal/kWh, while the average cost savings are Rp1,534,046,000/month.